A Structure-Function Mechanism for Schizophrenia - Vadakkan, Kunjumon I. (Frontiers in Psychiatry, 2012)
The multiple etiologies of schizophrenia prompt us to raise the question: what final common pathway can induce a convincing sense of the reality of the hallucinations in this disease? The observation that artificial stimulation of an intermediate order of neurons of a normal nervous system induces hallucinations indicates that the lateral entry of activity (not resulting from canonical synaptic transmission) at intermediate neuronal orders may provide a mechanism for hallucinations. Meaningful hallucinations can be de-constructed into an organized temporal sequence of internal sensations of associatively learned items, occurring in the absence of any external stimuli. We hypothesize that these hallucinations are autonomously generated by the re-activation of pathological non-specific functional LINKs formed between the postsynaptic membranes at certain neuronal orders and are examined as a final common mechanism capable of explaining most of the features of the disease. Reversible and stabilizable hemi-fusion between simultaneously activated adjacent postsynaptic membranes is viewed as a normal mechanism for functional LINK formation and is dependent on lipid membrane composition. Methods to remove the proteins that may traverse the hemi-fused membranes and attempts to replace the phospholipid side chains to convert the membranes to a near-normal state may offer therapeutic opportunities.